PRODUKSI TRICHOKOMPOS DARI KOTORAN SAPI - Nugraha, Zaskia Ema; Angelina, Angelina; Patamorgana, M. Surya; Martina, Wiwin; Afriatmei, Feny; Liana, Sesa Safitrah; Arfriandri, M.; Sapriansyah, Sapriansyah; Fahrurrozi, Fahrurrozi; Shafira, Baiq Alyandini; Ali, Muhammad (Jurnal Wicara, 2023)
The majority of the people of Bangket Parak Village still rely on the agricultural and animal husbandry sectors as a source of economic resilience. The current constraint in the agricultural sector is the availability of fertilizers, while in the livestock sector is the management of livestock waste. To overcome these two problems, the management of livestock waste as trichocompost fertilizer can be an alternative solution. The purpose of this activity is to provide education and skills to the community in making trichocompost fertilizer with livestock manure waste. The activity method consists of surveys, socialization activities, and demonstrations as well as assistance in making trichocompost fertilizer. In this socialization activity there are three stages including preparation, implementation, and reporting. This socialization activity began with a video screening. The activity continued with the presentation of socialization material. After that, demonstrations and assistance were carried out on how to make trichocompost fertilizer from utilizing livestock manure with the help of Trichoderma sp. The activity ended with the delivery of fertilizers to continue the fermentation process and the distribution of plant seeds to the participants. All participants who attended were very enthusiastic about following and listening to the entire series of events. It is hoped that through this activity, the community will gain new understanding and useful skills in overcoming the problems that are currently occurring.